Competition between specialized candidates - Stefan Krasa; Mattias Polborn (Center for Economic Studies and ifo Institute (CESifo), 2009)
We develop a formal model in which the government provides public goods in different policy fields for its citizens. We start from the basic premise that two office-motivated candidates have differential capabilities in different policy fields, and compete by proposing how to allocate government resources to those fields. The model has a unique equilibrium that differs substantially from the standard median-voter model. While candidates compete for the support of a moderate voter type, this cutoff voter differs from the expected median voter. Moreover, no voter type except the cutoff voter is indifferent between the candidates in equilibrium. The model also predicts that candidates respond to changes in the preferences of voters in a very rigid way. We also analyze under which conditions candidates choose to strengthen the issue in which they have a competence advantage, and when they rather compensate for their weakness.
Keywords: D72; 330; issue ownership; differentiated candidates; policy divergence; Ökonomische Theorie der Demokratie; Öffentliches Gut; Wahlkampf; Sachverständige; Theorie